Variasi Suhu Terhadap Pertumbuhan Neisseria Gonorrhoeae pada Media Coklat Agar Plate - Halimatussa ’diah; Urip Urip; Yunan Jiwintarum (Politeknik Kesehatan Kemenkes RI Jakarta I, 2017)
ABSTRACT Sexually transmitted infections (STI) are infections whose transmission is mainly through sexual intercourse. Gonorrhoeae is a disease that has a high incidence among sexually transmitted infections (STDs). The purpose of this study was to determine the effect of temperature variations on the growth of Neisseria gonorrhoeae. This study was pre-experimental with 6 treatments and 4 replications, namely heating water with direct inoculation to the media, without heating, temperature 40˚C, 50˚C, 60˚C, and 70˚C. It was examined by obtaining the results that from each treatment there was no colony growth on the Chocolate Agar Plate media. Those who experienced growth were only treated with direct inoculation on the media so that it could be concluded that there was no effect on the variation of water heating temperature on the growth of Neisseria gonorrhoeae on CAP media. Keywords : Neisseria gonorrhoeae, Growth, Temperature